Use of cardiac magnetic resonance imaging for alcohol septal ablation in hypertrophic obstructive cardiomyopathy. (June 2013) - Batton, Kyle; Moussa, Issam; Blackshear, Joseph; Mergo, Patricia; Austin, Christopher; Shapiro, Brian
Abstract This is a report of a 58-year-old man with severe hypertrophic obstructive cardiomyopathy who underwent alcohol septal ablation to relieve symptoms due to severe left ventricular outflow obstruction. Cardiac magnetic resonance was performed before and after the procedure. This case highlights the potential use of cardiac magnetic resonance imaging in the surgical planning of alcohol septal ablation as well as following the procedure to assess for complications and morphological changes.